Learning physics online or face-to-face: A case study of STEM and non-STEM students - Al-Zohbi, Gaydaa; Pilotti, Maura A. E.; Abdelsalam, Hanadi; Elmoussa, Omar (Frontiers in Psychology, 2022)
The academic performance of young women is particularly relevant to the success of societies that have only recently begun to address gender inequalities in education and the workforce. The present research examined the performance in a physics course of STEM and non-STEM female freshmen from such a society. It aimed to determine whether the change to online instruction, forced by the pandemic on students who had been accustomed to the face-to-face mode, affected their performance. In the study, performance on lab assignments and tests distributed across the semester (formative assessment measures) differed. Namely, STEM students performed better than non-STEM students on lab assignments and better online than face-to-face on tests. Non-STEM students’ performance on both lab assignments and tests remained insensitive to the mode of instruction. Performance on the final test and course grades, both of which were treated as summative assessment measures, replicated the pattern of effects exhibited by tests distributed across the entire semester. For all students, prior math proficiency made a limited contribution to performance. The findings of this study suggest that young women, who during the pandemic were brought back to the constraints of the home, were resilient in the face of change. According to physics instructors and students, by distributing study efforts more continuously in the online mode and taking advantage of recorded class meetings, they managed to promote performance (as per STEM students) or preserve it (as per non-STEM students).